Pengaruh Biaya Produksi, Biaya Pemasaran, Dan Penjualanterhadap Laba Bersihpada Perusahaan Manufaktursub Sektor Farmasi - masta Sembiring (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
The purpose of this study is to research, test, and analyze cost analysis, marketing costs, and net profit sales in Pharmaceutical Sub-Sector Manufacturing Companies listed on the IDX in 2013 - 2019. The type of research used in this research is quantitative research methods. The sampling technique used purposive sampling. The population in this study were 7 companies consisting of detailed data on production costs, marketing costs, sales and net profit of pharmaceutical sub-sector manufacturing companies which were listed on the Indonesia Stock Exchange in 2013-2019. The samples in this study were 7 years of annual reports and financial reports of pharmaceutical sub-sector manufacturing companies listed on the Indonesia Stock Exchange from 2013 to 2019 and 7 companies so that the total data amount was 49 samples. documentation study by collecting data in the form of secondary data from published annual reports. The data analysis technique used in this research is descriptive statistical analysis, multiple linear regression analysis, classical assumptions (normality test, autocorrelation test, multicollinearity test, and heteroscedasticity test) and hypothesis testing (partial test (t test), simultaneous test (test). f), Keywords: Current ratio, Debt to equity ratio, Return on equity, Price to book value.